Implementasi Teknik Kreatif Editing Dalam Pembuatan Video Promosi Wayang Sukuraga - Salsabilla, Tiara Zahsy; Burhanuddin, Burhanuddin (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Wayang Sukuraga is a traditional performing art from Sukabumi, West Java, that conveys strong moral and educational values. However, this art form remains relatively unknown, especially among younger generations. This final project aims to introduce and promote Wayang Sukuraga through digital media in the form of an engaging and communicative promotional video. The method used is Research and Development (R&D) with a 4D model approach (Define, Design, Develop, Disseminate). The main focus lies in the post-production stage, specifically the video editing process, which integrates creative techniques such as visual narrative arrangement, speed adjustment, color grading, audio processing, and scene transitions. This project was carried out in collaboration with the Department of Communication and Informatics (Diskominfo) of Sukabumi City and resulted in a 4-minute promotional video published through the partner's official social media channels. The final result shows that the application of creative editing techniques effectively enhances the visual appeal and communicates the cultural message to the public. This project serves as part of a contextual cultural preservation strategy that adapts to the dynamics of digital technology.